Beyond generations; a social housing community - Björkström, Linnea (My University, 2026)
Beyond Generations is a thesis that explores how architectural design, such as spatial organisation and the layout of shared spaces, can foster social interaction and a sense of community across multiple age groups. This is investigated through inter generational housing, in a context where age seg regation is becoming increasingly common. The thesis responds to societal challenges such as lone liness and isolation, age segregation and ageism, a shortage of affordable housing for young people and families and the growing need for alternative housing models for an ageing population. Grounded in theories of social sustainability and intergenerational practice, the project combines literature studies, semi-structured interviews and reference analyses with iterative design meth ods. The design process involves sketching, study visits and site analysis to develop spatial strategies that balance private and communal life, identify ing architectural elements that foster social inter action. The project results in a housing proposal in Goth enburg, Gamlestaden, that promotes well-being, belonging and everyday encounters between gen erations, while working to counteract loneliness. Shared environments and spatial organisation are thus strategically integrated into the complex to encourage daily social interaction between res idents and strengthen the sense of community among neighbours, while maintaining possibilities for privacy and allowing residents to choose their level of engagement. This is achieved through the concept of a social corner, which concentrates circulation and shared functions within the building around a node, creating focal points for interaction through permeability between shared spaces. As well as by the implementation of transition zones located at the thresholds between the different degrees of privacy, creating a gradual shift from communal to private as you move through the building. The project thus contributes to the discussion on socially sustainable housing by proposing architectural strategies that support intergenerational relationships and social interaction in everyday communal life.